Perbandingan Upah Tenaga Kerja Antara Kontraktor dan PERMEN PU 2016 pada Pekerjaan Konstruksi Baja Proyek Gedung Fakultas Ilmu Pendidikan Universitas Tribhuwana Tunggadewi Malang - Nggiku, Yusman Umbu ; Suhudi; Wijaya, Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Steel construction job wages System in particular the steel column is a system or method used to set up and manage a steel construction projects ranging from planning up to its implementation. The purpose of the research on steel columns, this job is to know the results of the comparison of wage workers unit price where a more efficient method of contracting with wages method PERMEN PU 2016. In this thesis the author calculates the cost budget plans Project Construction Faculty of Education UNITRI Malang between AHSP contractors with PERMEN PU 2016. The coefficients used analysis units of workers contracting method and the method of PERMEN PU 2016 is same. The results of the comparison analysis of steel construction job wages are the construction of the Faculty of education was especially UNITRI steel columns retrieved results calculation planning cost budget methods of Contractor Registration Rp 45,455,256.84 and PERMEN PU 2016 registration Rp 54,156,803.01. The price difference is obtained from the calculation of the steel column of this analysis proved that the contractors more efficiently than on analysis of PERMEN PU 2016.